Residents satisfaction towards affordable housing on physical and social dimension in Kluang, Johor / Nur Shahidah Mohd Zailan - Mohd Zailan, Nur Shahidah (2023)
The provision of affordable housing in Malaysia is increasing as to response to the encouragement of home ownership to all Malaysian by the government specifically for middle- and lower-income group. However, most of the affordable housing provided does not meet the requirement of a good quality of housing in so many aspects. Hence, in this research, the resident's satisfaction towards affordable housing has been investigated. From the previous research, physical and social dimension of housing satisfaction has been mentioned frequently, thus the researcher was only focused on these two elements to see how it contributes to the resident's satisfaction level. The objectives of this research are to identify what are the elements of residential satisfaction in affordable housing and to determine the level of resident's satisfaction towards the affordable housing in the physical and social dimensions, where this research has been taken place at Rumah Mampu Milik Johar (RMMJ), Taman Kluang lndah, Kluang that has aged more than 10 years. The case study selection was based on the concept of performance tool used in this research which is Post-Occupancy Evaluation (POE), whereby explain the suitability of the case study for this research.